Solenoid actuated Five-fingered robotic hand design: evaluating the capability of solenoid actuators in generating basic finger motions - Syed Zainal Abidin Syed Kamarul Bahrin; Khairul Salleh Mohamed Sahari (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
There are numerous robotic hand designs but the five-fingered robotic hand design is the most dexterous robotic hand design due to its similar appearance and motions with the human hands. The fingers' motions are commonly driven by geared motors or other types of emerging technologies. However, the motions are yet to be driven directly by solenoid actuators due to its limited stroke length and also general perceptions of its applications as an actuator. Nevertheless, solenoid actuators are known for their fast reaction time and strong holding force which are useful to generate fast motions and strong grasping actions. To realise this concept, previous research and developments had been done by the authors but the outcome was not convincing enough due to the absence of a working prototype. Therefore, this paper introduced a new solenoid actuated robotic hand design and its prototype. The prototype was then tested and evaluated in accordance to the operational concept where the findings showed that the solenoid actuators were capable of generating basic finger motions.